Given the expressions for \( C \) and \( D \):
\[ C = 2x - 5x^2 - 9 \] \[ D = x^2 + 9x \]
We need to find \( 3C + 2D \).
First, we calculate \( 3C \):
\[ 3C = 3(2x - 5x^2 - 9) \] \[ = 6x - 15x^2 - 27 \]
Next, we calculate \( 2D \):
\[ 2D = 2(x^2 + 9x) \] \[ = 2x^2 + 18x \]
Now we can add \( 3C \) and \( 2D \):
\[ 3C + 2D = (6x - 15x^2 - 27) + (2x^2 + 18x) \]
Now we combine like terms:
-
For \( x^2 \) terms: \[ -15x^2 + 2x^2 = -13x^2 \]
-
For \( x \) terms: \[ 6x + 18x = 24x \]
-
The constant term: \[ -27 \]
Putting it all together, we have:
\[ 3C + 2D = -13x^2 + 24x - 27 \]
Thus, the expression \( 3C + 2D \) in standard form is:
\[ -13x^2 + 24x - 27 \]